Analgesic effects of lidocaine-ketorolac compared to lidocaine alone for intravenous regional anesthesia - Shahram Seyfi; Nadia Banihashem; Ali Bijani; Karimollah Hajian-Tilaki; Mohsen Daghmehchi (Babol University of Medical Sciences, 2018)
Background: Intravenous regional anesthesia is a simple and reliable method for upper extremity surgery. In order to increase the quality of blocks and reduce the amount of pain, many drugs are used with lidocaine. In this study, the effect of ketorolac-lidocaine in intravenous regional anesthesia was investigated. Methods: 40 patients undergoing elective upper limb with America Society of Anesthesiologists class I and II were selected and randomly divided into two groups. The first group of 20 patients received 200 mg of lidocaine, and the second group, 200 mg of lidocaine with 20 mg of ketorolac. In both groups, the drug was diluted to 40 ml. In both groups, the onset of sensory block, onset of tourniquet pain, the onset of pain after opening the tourniquet, score of postoperative pain and analgesic prescription in the first 24 hours, during 1, 6, 12 and 24 hours were studied. A measure of the quality of analgesia was evaluated by VAS. Results: The mean onset of tourniquet pain in the two groups was not significantly different (P=0.443). In the ketorolac group, the onset of pain after opening the tourniquet was significantly longer than lidocaine group (p<0.001). The mean postoperative pain score during the first 24 hours after surgery in the ketorolac group was significantly lower than lidocaine group (p<0.001). The average number of analgesia prescription during the 24 hours after operation was significantly lower in ketorolac group than lidocaine group (p<0.001). Conclusions: Adding ketorolac to lidocaine for regional anesthesia can reduce the postoperative pain for up to 24 hours after opening the tourniquet.